Application of component method on partial strength connections connected by thick plate between column flanges - Md. Tahir, Mahmood (2012)
Traditional beam connections to the minor axis of a column have relatively low strength and stiffness. A modified detail, using a plate welded between the toes of the column flange - referred to as a toe plate connection - is examined in this paper. The results of an experimental investigation for both flush and extended end-plate connections connected to a 25 mm thick end-plate are presented. The tests are complemented by finite element modelling which compares very well with the test observations. The results show a significant increase in both moment resistance and initial stiffness for this connection detail compared with connections made directly to the column web. This offers the prospect of more optimal solutions taking advantage of partial strength frame design for the minor axis as well as major axis.